PENGARUH KEAHLIAN AKUNTANSI DAN KEAHLIAN KEUANGAN PADA KOMITE AUDIT DAN DEWAN KOMISARIS TERHADAP MANAJEMEN LABA - Ulfah Hariani; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2020)
ABSTRACTThis study aims to determine the effect of accounting expertise and financial expertise of audit committee and the board of commissioners on earnings management. The sampling method uses purposive sampling technique, the samples obtained were 34 manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2016-2018. The data analysis method used is moderated regression analysis. The results of this study simultaneously prove the independent variables audit committee accounting skills, board of commissioners accounting skills, audit committee financial skills, and board of commissioners financial skills influences earnings management, but partially the influence of accounting expertise and financial expertise of audit committee and the board of commissioners does not affect earnings management. This is due to the fact that the formation of the audit committee and the board of commissioners is only based on applicable regulations.Keywords: Audit Committee Accounting Skills, Board of Commissioners Accounting Skills, Audit Committee Financial Skills, Board of Commissioners Financial Skills, Earnings Management.